(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2014)
Several factors can be identified as the origin of the current economic crisis. Among them are some practices that have in the past and are still now severely damaging capital markets. In this paper we will specifically mention three: deficiencies inthe application of financial formulae, improper use of derivative instruments and inadequate attempts to solve problems carried out during the last thirty years. This lack of exemplarity practices is reflected in cases like the Barings Bank, Enron. AIG or Madoff among others we will refer to. It has not onlybeen a case of excessive and improper use of financial formulae, but also one of fraud scandals and lack of transparency. Although there has been attempts from the authorities to establish legal reforms and recommendations, little has been carried out and not always very efficiently. It is necessary to think about a consistent and coordinated regulatory framework on this matter.